Inflammatory myofibroblastic tumor in pediatric patients: challenges in diagnosis, multidisciplinary management, and surgical strategies - Izchel Valdez García; Alejandro Solano Gutierrez; Sofia Brenes Guzmán; Brenda Aguilar Viveros (SpringerOpen, 2024)
Abstract Background Inflammatory myofibroblastic tumor is a rare yet profoundly impactful condition, particularly within the pediatric population. This case report illuminates the intricate challenges of diagnosing and managing inflammatory myofibroblastic tumors in children, underscoring the importance of interdisciplinary collaboration in formulating effective treatment strategies. Notably, the choice of surgical approach holds a paramount influence on the risk of recurrence and metastasis, with wide resection with bronchotomy, lobectomy, and pneumonectomy demonstrating significantly diminished recurrence rates compared to wedge resection in bronchoscopic removal. Case presentation We present the case of a 3-year-old girl with a progressive, nonproductive cough, occasionally accompanied by episodes of hemoptysis and pneumonia for a year, secondary to an inflammatory myofibroblastic tumor that was removed by bronchotomy with excellent results. Conclusion Given the extraordinary rarity of this disease in pediatric patients, ongoing research endeavors and the accumulation of collective expertise are paramount.